EFFECTIVENESS OF BIOFLOC, PROBIOTICS AND THE COMBINATIONS ON GROWTH, IMMUNE RESPONSES AND RESISTANCE OF VANNAMEI SHRIMP INFECTED WITH Vibrio parahaemolyticus - Wicaksono, Baref Agung; Widanarni, Widanarni; Yuhana, Munti; Gustilatov, Muhamad; Afiff, Usamah (Indonesian Aquaculture Journal, 2025)
Vibrio parahaemolyticus strain that produces PirA and PirB toxins is the main causative agent of Acute Hepatopancreatic Necrosis Disease (AHPND) in vannamei shrimp. This study aimed to evaluate the effect of biofloc application, probiotic Pseudoalteromonas piscicida 1Ub, and their combination on growth, immune response and resistance of vannamei shrimp infected with V. parahaemolyticus strain. This study used a completely randomized design consisting of biofloc-based system treatment with or without probiotic 1Ub and normal seawater as control. All treatment groups were challenged with V. parahaemolyticus AHPND strain at a cell density of 105 CFU mL”1 through immersion, while the negative control was reared without being pathogenic challenged. The shrimp used were in averaged body weight of 1.3 ± 0.002 g, reared for 21 days and fed five times a day at 06:00, 10:00, 14:00, 18:00, and 22:00 WIB. The results showed that the B+Pro combination challenge test treatment resulted the best growth performance (specific growth rate, absolute length gain and feed conversion ratio) (P<0.05) compared to other challenge test treatments. hrimp treated with B+Pro also showed a lower intestinal cell population of V. parahaemolyticus RfR, and significantly higher immune response values (P<0.05) than those of other challenge test treatments and K+. Furthermore, those parameters supported positive impact on final shrimp survival rates in the experiment. This study shows that the application of combination of biofloc and 1Ub probiotic bacteria can significantly protect and increase the resistance of vannamei shrimp to V. parahaemolyticus AHPND infection.